Indonesia Persepsi Petani Terhadap Perbankan Syariah Di Nagari Pandai Sikek - Muhammad Farel Rizky; Rusydi Fauzan; Ali Rahman; Yefri Joni (UNCANG : Journal of Sharia Banking and Islamic Finance, 2025)
This research is motivated by the fact that many farmers prefer to borrow funds from conventional banks or through traditional systems due to limited information, a lack of understanding of Islamic contracts (akad), and diverse perceptions toward Islamic banking. The purpose of this study is to analyze farmers’ perceptions of Islamic banking in Nagari Pandai Sikek and to identify the factors influencing those perceptions. The study employs a descriptive qualitative method with a field research approach, which allows the researcher to deeply understand farmers’ perceptions, views, and experiences regarding Islamic banking based on real conditions in the field. This approach emphasizes the meaning behind farmers’ behaviors and opinions rather than merely focusing on numerical or statistical data. Data were collected through interviews, observations, and documentation involving 40 informants from four sub-villages (jorong) in Nagari Pandai Sikek. The findings reveal that farmers’ perceptions of Islamic banking remain diverse and not entirely positive. Out of 360 responses, 34.17% were positive (123 responses), 29.17% were neutral (105 responses), and 36.66% were negative (132 responses). The highest negative perception was found in the value variable (44.16%), as many farmers believed that the Islamic financing system is not significantly different from conventional banking due to burdensome installments and complex procedures. In the information variable, negative perceptions reached 35%, mainly caused by the lack of socialization and Islamic financial literacy. Meanwhile, the education variable recorded the highest positive perception at 36.67%, indicating that education level and religious understanding help farmers comprehend the principles of Islamic banking.This study concludes that Islamic banks need to enhance socialization, education, and product innovation to make their services more relevant to the needs of rural farmers.